Labor Organization and Labor Politics, 1827-37 - Commons, John R. (Quarterly Journal of Economics, 1907)
Journal Article Labor Organization and Labor Politics, 1827–37 Get access John R. Commons John R. Commons University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 2, February 1907, Pages 323–329, https://doi.org/10.2307/1883436 Published: 01 February 1907